The Influence of Self-Efficacy, Locus of Control, and Quality of Work Life on Employee Performance - Atikah Haasyimiyah; Suhana Suhana (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research tries to find out how self-efficacy, locus of control, and quality of work life impacts employee performance. The subjects of the study were the permanent employees of PT. Sampharindo Perdana located at Semarang. The sample size was determined through convenience sampling method which yielded 147 respondents. The research data was obtained through questionnaire surveys and analyzed with SPSS 22. The methodology employed were descriptive analysis, validity test, reliability test, determination test, F test, and T test. This study validates and concludes that self-efficacy and quality of work life have a significant positive impact on employee performance whereas locus of control does not significantly impact employee performance. The purpose of this study was to provide practical contributions while addressing the gap between theoretical perspectives and actual application concerning the psychological and environmental parameters affecting performance in a pharmaceutical company.